PERKAWINAN SEJENIS DALAM KONSTRUKSI TEORI MASHLAHAH - Fajar Wajdu (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2019)
AbstractThis study uses the Mashlahah approach in explaining the similar legal position of marriage. Based on the consideration of the maslahah by paying attention to the objectives of Islamic law, which is to withdraw maslahah and reject mudharat, similar marriage is in fact contrary to the purpose of the fourth Islamic law, namely raising offspring. Therefore, Islam strictly prohibits marriage not only because it is against the Shari'a, but also contrary to the nature of humans who tend to live in pairs, precisely tend to the opposite sex.Similar marriage or similar sex (homosexual) is a deviant behavior that is very cruel and transcending, which is beyond the limits of the divine will of human nature. Then similar marriage is forbidden in Islam because it not only has a negative impact on the individual, but also ruining community life. Because the reluctance of marriage to the opposite sex is just the same as destroying the survival of humans on the earth, because it has become a sunnatullah that it is impossible to create a generation of humans from same-sex marriage. So the logic of marriage in Islam is with the opposite sex (heterosexual) and not the same sex marriage (homosexual) that justifies liwat.Keywords: Similar Marriage; Sexuality; Maslahah.